Insulator dysfunction and oncogene activation in IDH mutant gliomas - Flavahan, William A.; Drier, Yotam; Liau, Brian B.; Gillespie, Shawn M.; Venteicher, Andrew S.; Stemmer-Rachamimov, Anat O.; Suvà, Mario L.; Bernstein, Bradley E. (Nature (London), 2016)
An epigenetic mechanism in which gain-of-function IDH mutations promote gliomagenesis by disrupting chromosomal topology is presented, with IDH mutations causing the binding sites of the methylation-sensitive insulator CTCF to become hypermethylated; disruption of a CTCF boundary near the glioma oncogene PDGFRA allows a constitutive enhancer to contact and activate the oncogene aberrantly. IDH mutant gliomas characterized Cancer genome sequencing studies have identified recurrent IDH mutations in brain tumours and other cancers. IDH mutant gliomas have altered DNA methylation landscapes, such as hypermethylation of CpG island promoters. Here, Brad Bernstein and colleagues show that the effects of IDH1 mutation in gliomas are not limited to CpG islands, and the binding sites of the methylation-sensitive insulator CTCF are also hypermethylated. Disruption of a CTCF boundary near the glioma oncogene PDGFRA allows a constitutive enhancer to aberrantly contact and activate it. IDH mutations can therefore promote gliomagenesis by disrupting chromosomal topology and allowing aberrant gene regulatory interactions. Gain-of-function IDH mutations are initiating events that define major clinical and prognostic classes of gliomas 1 , 2 . Mutant IDH protein produces a new onco-metabolite, 2-hydroxyglutarate, which interferes with iron-dependent hydroxylases, including the TET family of 5′-methylcytosine hydroxylases 3 , 4 , 5 , 6 , 7 . TET enzymes catalyse a key step in the removal of DNA methylation 8 , 9 . IDH mutant gliomas thus manifest a CpG island methylator phenotype (G-CIMP) 10 , 11 , although the functional importance of this altered epigenetic state remains unclear. Here we show that human IDH mutant gliomas exhibit hypermethylation at cohesin and CCCTC-binding factor (CTCF)-binding sites, compromising binding of this methylation-sensitive insulator protein. Reduced CTCF binding is associated with loss of insulation between topological domains and aberrant gene activation. We specifically demonstrate that loss of CTCF at a domain boundary permits a constitutive enhancer to interact aberrantly with the receptor tyrosine kinase gene PDGFRA , a prominent glioma oncogene. Treatment of IDH mutant gliomaspheres with a demethylating agent partially restores insulator function and downregulates PDGFRA . Conversely, CRISPR-mediated disruption of the CTCF motif in IDH wild-type gliomaspheres upregulates PDGFRA and increases proliferation. Our study suggests that IDH mutations promote gliomagenesis by disrupting chromosomal topology and allowing aberrant regulatory interactions that induce oncogene expression.